Implementasi Pendidikan Karakter dalam Mata Kuliah Pendidikan Kewarganegaraan - Ginting, Seriwati (Zenit, 2015)
Nowadays, moral education or character education is seen as something urgent. Moral education in Indonesia is inseparable from civic education. The events that occur in our county hasinspired and reminded the nation of the importance of education for the human character. Multidimensional crisis has affected the material and spiritual development of this nation. In such conditions, it is culture that is often seen to be violent, or corrupt. When there is an opportunity, there will be demonstration of anarchists, or anti- establishment. There is even an imbalance between reason and emotion. It is known that without moral education everything that is done will not bebeneficial to the nation and the country. One of the added values of character education is it can be implemented in real life. The values that have been studied in college are to be realized in life. As stated by Thomas Lickona that character education is character education by itself because itinvolves the aspects of knowledge (cognitive), feeling and action. The question is how moral values can be implemented in our daily lives?Keywords: Character education, implementation, moral values, citizens